57.6k views
4 votes
A^3b^-4/a^2b^3a^-5 write without rational notation and move all terms to numerator

User Edison
by
4.8k points

1 Answer

3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{a^3b^(-4)}{a^2b^3a^(-5)}\implies \cfrac{a^3}{1}\cdot b^(-4)\cdot \cfrac{1}{a^2}\cdot \cfrac{1}{b^3}\cdot \cfrac{1}{a^(-5)}\implies a^3\cdot b^(-4)\cdot a^(-2)\cdot b^(-3)\cdot a^5 \\\\\\ a^3a^5a^(-2)b^(-4)b^(-3)\implies a^(3+5-2)b^(-4-3)\implies a^6b^(-7)

User Alexander Samoylov
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.